2005
DOI: 10.1038/nm1325
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Stat3 signaling in the hematopoietic system elicits multicomponent antitumor immunity

Abstract: The immune system can act as an extrinsic suppressor of tumors. Therefore, tumor progression depends in part on mechanisms that downmodulate intrinsic immune surveillance. Identifying these inhibitory pathways may provide promising targets to enhance antitumor immunity. Here, we show that Stat3 is constitutively activated in diverse tumor-infiltrating immune cells, and ablating Stat3 in hematopoietic cells triggers an intrinsic immune-surveillance system that inhibits tumor growth and metastasis. We observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
861
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 926 publications
(914 citation statements)
references
References 43 publications
35
861
3
5
Order By: Relevance
“…We have demonstrated that loss of STAT3 in DCs blocked Flt3, but not GM-CSF signaling for DC differentiation, which consequently significantly affects T cell differentiation and activation (unpublished results). In consistency with this idea, a recent report revealed that STAT3 in DCs is involved in production of T regs during tumorigenesis [84].…”
Section: The Roles Of T Regulatory Cells and Dendritic Cells In Ibds mentioning
confidence: 65%
“…We have demonstrated that loss of STAT3 in DCs blocked Flt3, but not GM-CSF signaling for DC differentiation, which consequently significantly affects T cell differentiation and activation (unpublished results). In consistency with this idea, a recent report revealed that STAT3 in DCs is involved in production of T regs during tumorigenesis [84].…”
Section: The Roles Of T Regulatory Cells and Dendritic Cells In Ibds mentioning
confidence: 65%
“…*P Ͻ 0.05; **P Ͻ 0.01. topoietic cells triggers an intrinsic immune-surveillance system that inhibits tumor growth and metastasis. 30 We previously identified inflammatory cell infiltration in tumor areas of CCSP-rtTA/(tetO) 7 -CMV-Stat3C bitransgenic mice. 1 How these cells contribute to tumor formation is not known.…”
Section: Discussionmentioning
confidence: 98%
“…pSTAT3, which has antagonistic effect on pSTAT1 (27,28), plays a key role in suppressing the function of neutrophils, NK cells, DCs (31)(32)(33) and negatively regulating the Th1-mediated inflammatory response (30,31). Therefore, the balance of pSTAT1 and pSTAT3 plays an important role in regulating immune response and maintaining immunohomeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…pSTAT3, which has antagonistic effect on pSTAT1 (27,28), is not only a potent negative regulator of the Th1-mediated inflammatory response, but also an activator of many genes that are crucial for immune regulation (29,30). Down-regulation of STAT3 could enhance Th1 type immune response and activate DCs, NK cells and macrophages (31)(32)(33). So the balance of pSTAT1 and pSTAT3, which has been studied in cancer immunity (31,34), has an important role in regulation of immune responses.…”
Section: Introductionmentioning
confidence: 99%